2021
DOI: 10.1037/emo0000936
|View full text |Cite
|
Sign up to set email alerts
|

Gratitude reduces consumption of depleting resources.

Abstract: Sustaining finite public resources presents a dilemma between acting in self-interest for present benefit versus working toward long-term collective gain. Given gratitude’s links to prosociality and self-control, the present studies investigated whether gratitude would promote sustainable resource extraction under conditions of rapidly depleting resources. In Study 1 (N = 155), participants were randomly assigned to experience an emotional state (gratitude or neutral) prior to playing a resource dilemma game i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…DeSteno et al (2019) conducted a behavioral experiment both in an online and a laboratory setting, indicating that participants in a grateful state of mind exhibited fewer impulsive behaviors compared to those in the neutral and happiness groups. Individuals in a state of gratitude tended to exhibit less energy-wasting behavior (Kates & DeSteno, 2021), which suggested self-control regarding energy use. Inhibitory control contributes significantly to disciplined behavior by enabling individuals to resist impulsive actions.…”
Section: Discussionmentioning
confidence: 99%
“…DeSteno et al (2019) conducted a behavioral experiment both in an online and a laboratory setting, indicating that participants in a grateful state of mind exhibited fewer impulsive behaviors compared to those in the neutral and happiness groups. Individuals in a state of gratitude tended to exhibit less energy-wasting behavior (Kates & DeSteno, 2021), which suggested self-control regarding energy use. Inhibitory control contributes significantly to disciplined behavior by enabling individuals to resist impulsive actions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that gratitude promotes sustainable resource extraction under the condition of rapidly depleting resources (Kates & DeSteno, 2021). A generally positive emotional state could not explain this effect; therefore, gratitude might help producing sustainable behavior.…”
Section: Heartfulness and Sustainabilitymentioning
confidence: 97%
“…Previous studies have shown that gratitude, as a transpersonal positive emotion, can motivate individuals to take a long-term development vision in economic decisions or tasks that require self-control, such as intertemporal decision-making and public goods games ( DeSteno et al, 2014 ; Kates and DeSteno, 2021 ). Grateful individuals would delay immediate gain, promote sustainability and reduce the over-consumption of public resources ( DeSteno et al, 2014 ; Kates and DeSteno, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that gratitude, as a transpersonal positive emotion, can motivate individuals to take a long-term development vision in economic decisions or tasks that require self-control, such as intertemporal decision-making and public goods games ( DeSteno et al, 2014 ; Kates and DeSteno, 2021 ). Grateful individuals would delay immediate gain, promote sustainability and reduce the over-consumption of public resources ( DeSteno et al, 2014 ; Kates and DeSteno, 2021 ). Recent studies have indicated that participants’ gratitude to nature can expand the function of gratitude for the sustainable use of economic resources to the function of preserving natural resources ( Naito et al, 2010 ; Zelenski and Desrochers, 2021 ; Jacobs, 2022 ; Tam, 2022 ).…”
Section: Introductionmentioning
confidence: 99%